LINES SELECTION TO DETERMINE THE CHEMICAL COMPOSITION OF STARS IN THE RANGE -3 <= [FE/H] <= -0.7 - Basak, N. Yu.; Mishenina, T. V. (Одеські астрономічні публікації, 2012)
Using the spectra obtained with echelle spectrograph SOPHIE (1.93 m telescope, OHP, France) and the data from about 20 papers of various authors, we have compiled a list for around four thousand lines of different chemical elements. Based on the spectra of the Sun and stars and also synthetic spectrum calculations in different ranges of metallicity, we selected 300 unblended lines of FeI, FeII and 200 lines of YII, ZrI, ZrII, LaII, CeII, PrII, NdII, SmII, GdII, that are recommended for the study of the chemical composition.